The Swallowing and Voicing Characteristics of Pharyngeal Dystonia: A Single Case Report - Loren Kahn; Heila Jordaan (South African Journal of Communication Disorders, 2001)
This paper describes the swallowing difficulty and abnormal voicing characteristics of a subject with pharyngeal dystonia. This rare form of dystonia, considered to be a neurological condition resulting in involuntary spasm of the muscles of the pharynx, has not been documented in terms of its effects on the acoustic properties of the voice. This study revealed that during pharyngeal spasm, there are significant delays in voice onset time, a reduction in fundamental frequency, an increased percentage of sub-harmonics and variability in the amplitude perturbation quotient as well as shimmer. There was also evidence of these characteristics during periods of 'spasm-free' voice production, suggesting that the condition might be more consistent than what the subject described. Resonance disturbances were observed in spasm, which might explain the 'hollow' and affected voice quality. The subject also reported severe swallowing difficulties during the periods of spasm, characterised by a tight constriction at the level of the subject's throat. It is clear that an abnormality at the level of the cricopharyngeal muscle has a dual effect on the acoustic properties of the voice and on swallowing.